Co-producing and co-assessing a new service solution for enhancing health and social care integration: a participatory research protocol - Eleonora Gheduzzi; Mariarosaria Savarese; Alberto Mangini; Silvia Mitidieri; Michele Paleologo; Cristina Masella; Guendalina Graffigna (BMC, 2024)
Abstract Background This paper describes a study protocol for co-producing and co-assessing a new sustainable and scalable service solution that enhances health and social integration by involving providers and volunteers delivering services for elderly people in the province of Cremona (Italy), where the elderly population will reach 27% in 2023. Methods This upcoming study involves mixed-method participatory research and is structured in three study phases and related objectives. First, it will co-produce a new, accessible and sustainable service solution using an iterative design and management method, Plan-Do-Check-Act by involving professionals and volunteers of a heterogeneous group of health, social and third sector organizations located in the city of Cremona (Italy). Second, the study protocol will co-assess the outcomes of the new service solution using a mixed-method approach for measuring the outcomes on: professionals and volunteers (micro level) and their health, social and third sector organizations (meso level). Third, this study will co-investigate the scalability of the new solution promoting health and social integration in other similar urban areas of the Province of Cremona via the Intervention Scalability Assessment Tool (macro level). The data will be collected through the analysis of official documents, websites, policies and participatory workshops. Discussion This protocol proposes an innovative intervention, a novel participatory approach, and an unexplored scalability assessment tool in the context of health and social care integration. This study aims to support professionals from health and social care service providers and volunteers from third-sector organizations to collaborate and integrate each other's resources. In doing so, the participatory approach will facilitate the co-creation of an effective response to the need of health and social integration, and the development of trustful relationships between health and social care service providers. Moreover, the adoption of Plan-Do-Check-Act and Intervention Scalability Assessment Tool will ensure the quality, scalability and sustainability of the new service solution in other settings.